The Coptic life of Aaron : critical edition, translation and commentary - Dijkstra, Jitse H. F.; Dijkstra, Jitse H. F.; Vliet, Jacques van der, 1952-; Vliet, Jacques van der, 1952- (Vigiliae Christianae, Supplements, 2020)
"The Life of Aaron is one of the most interesting and sophisticated hagiographical works surviving in Coptic. The work contains descriptions of the lives of ascetic monks, in particular Apa Aaron, on the southern Egyptian frontier in the fourth and early fifth centuries, and was probably written in the sixth century. Even though the first edition of this work was already published by E.A. Wallis Budge in 1915, a critical edition remained outstanding. In this book Jitse H.F. Dijkstra and Jacques van der Vliet present not only a critical text, for the most part based on the only completely preserved, tenth-century manuscript, but also a new translation and an exhaustive commentary addressing philological, literary and historical aspects of the text".